(untitled) (International Journal of Food and Nutritional Sciences, 2019)
The alternative dispute resolution techniques in India have been gaining a greater significance since the Arbitration and Conciliation Act, 1996 and the Commercial Courts Act, 2015. The recent codified law of the Mediation Act, 2013 marks a landmark event in developing the jurisprudence of mediation by codifying the procedure of appointment of mediators, ensuring timely resolution of the disputes, and also details of which disputes are exempted from mediation.